Towards NFC-Aware Process Execution for Dynamic Environments - Hamann, Kristof; Steenbuck, Sebastian; Zaplata, Sonja (Electronic Communications of the EASST, 2011)
A flexible execution of business processes requires to deal with dynamic environments and to adapt to specific situations detected at runtime. However, flexibility needs to be restricted in a reasonable way which fits the requirements of the process initiator. An important aspect is the specification of user-defined constraints with respect to the non-functional characteristics (NFCs) of the execution. However, most existing approaches for such descriptions and corresponding service selection mechanisms are computationally complex and thus hinder a flexible runtime distribution of the process including resource-restricted clients such as, e.g., mobile devices.This paper addresses the problem of NFC-aware process execution in such dynamic environments. Therefore, the paper presents an NFC meta-model and a corresponding language to support process modelers in expressing their non-functional requirements in a way which facilitates runtime decomposition and to dynamically derive local NFC specifications from remaining global requirements on process level by more simple heuristic approaches. Based on that, an initial algorithm is introduced in order to evaluate NFCs during runtime.